Anthropometric and physical characteristics of motor disabilited Paralympic rowers - Caldas Porto, Y.; Almeida, M.; de Sa, C. K.; Schwingel, P. A.; Zoppi, C. C. (Research in Sports Medicine, 2008)
The purpose of this study was to characterize aerobic, anaerobic, handgrip strength, and body fat content (BF) characteristics in paralympic rowers (ROW) in order to determine motor disabled rowers' fitness level and if specific motor disabilities could impair performance in this specific population. Upper body anaerobic threshold (LacT), peak (PK-AnP), mean (M-AnP), and lower (L-AnP) anaerobic power, peak anaerobic power to weight ratio (RelPk-AnP) and fatigue index (FI) were measured by the Wingate test (WinT). Handgrip strength was also measured and skinfold sum was used to estimate BF and were compared with a reference group of recreational disabled athletes (CON). LacT was significantly higher (p < 0.01) in ROW compared with CON. RelPk-AnP and BF were significantly different (p < 0.05) in ROW compared with CON as well. All other measured parameters did not significantly differ between ROW and CON. In most of cases, rowers have shown a relative low performance level, induced probably by specific disabilities.